Understanding the tensile fracture of deeply-notched metallic glasses. (15th December 2020) - Yang, Guannan; Qu, Ruitao; Xu, Guangdong; Li, Quanzhen; Cui, Chengqiang; Zhang, Zhefeng
Graphical abstract: Highlights: Ellipse criterion theory clarifies the deep notch enhancement mechanism in MGs. Highly dispersed and relatively low stress/strain field near the notch is revealed. Positive third principal stress will result in increased failure angle and strength. A shear to tensile failure mode transition is predicted at the center of the notch. Parameter Δ can provide an effective index to predict the failure mode of MGs. Abstract: Deeply-notched metallic glasses can achieve significantly enhanced nominal tensile strain and strength under tension, and show the characteristics of dimples and "cup-and-cone" morphology on the fractographs. It has been expected that this deep-notch enhancement effect is resulted from the suppressed shear banding. In this study, we provided another interpretation for this effect through stress/strain field analyses based on the ellipse criterion. The results revealed the existence of relatively low but highly dispersed stress/strain instead of highly enhanced and localized stress/strain in deeply-notched metallic glasses, and therefore the actual stress is much lower than the nominal value. Owing to the positive third principal stress condition, the failure angle predicted by the ellipse criterion shifted from 45° at the edge of the notch to 90° at the center of the specimen, which was consistent with the "cup-and-cone" fracture morphology. These findings clarify the very high nominal stress/strain and special fracture process in deeply-notched metallic glasses. Our work provides a useful method to predict the shear-to-tensile failure mode transition of metallic glasses under complex loading conditions.